2018
DOI: 10.1097/fch.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Voices of the Filipino Community Describing the Importance of Family in Understanding Adolescent Behavioral Health Needs

Abstract: Filipinos are a large, yet invisible, minority at high risk for adolescent behavioral health problems. Limited research describes the family as offering a source of positive support for some Filipino youths and yet for some it is also a source of stress and isolation, leading to struggles with adolescent depression and suicidal behavior. This article describes a qualitative study that investigates the role of family when understanding behavioral health needs among Filipino adolescents. Findings highlight the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Research examining disruptions in the family because of parental migration reveal experiences of economic challenges, emotional problems, and poor health [ 40 , 41 , 42 ]. Where family cohesion is present, Filipino adolescents felt supported, had great academic ambitions, and mental health [ 43 ]. In our study, family disruptions often took place during times of war with some of the youth never reuniting with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining disruptions in the family because of parental migration reveal experiences of economic challenges, emotional problems, and poor health [ 40 , 41 , 42 ]. Where family cohesion is present, Filipino adolescents felt supported, had great academic ambitions, and mental health [ 43 ]. In our study, family disruptions often took place during times of war with some of the youth never reuniting with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cultural emphasis on AsA family interdependence (Kim et al, 2001), family involvement, which has been shown to enhance youth psychotherapy efficacy in general (Haine-Schlagel & Walsh, 2015), might also increase treatment engagement for AsA youth (Sandil, 2006). Consistent with this possibility, qualitative evidence suggests that improving family cohesion during treatment is beneficial for the behavioral health of AsA youth (e.g., Filipino youth; Javier et al, 2018).…”
Section: Family Involvementmentioning
confidence: 98%
“…For the present study, we chose to conduct focus groups with adult participants because the definition to be developed would have to resonate with parents and caregivers first due to their place of authority and influence within the family hierarchy to seek and consent to the utilization of mental health services by their adolescents (Javier et al, 2018).…”
Section: Stigmatization Shame and Hiyamentioning
confidence: 99%